Should Treatment of Diabetic Foot Osteomyelitis Be Based on Bone Biopsies?. (July 2019) - Heidari, Nima; Kwok, Iris; Vris, Alexandros; Charalambous, Alexander
Recommendation: Yes. Bone biopsies play both a crucial diagnostic and interventional role in the management of diabetic foot infection. Although bone biopsies are not required in every case of diabetic foot infection, their most important role is in guiding accurate antibiotic treatment, as they provide more accurate microbiological information than superficial soft tissue samples in patients with diabetic foot osteomyelitis. Level of Evidence: Moderate. Delegate Vote: Agree: 100%, Disagree: 0%, Abstain: 0% (Unanimous, Strongest Consensus)